Implementation of Student Community Service Program to Instill Nationalism in the Young Generation - Muzfirah, Suci; Wandi, Wandi (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2024)
Community service is a strategic effort to instill nationalistic values in the younger generation, particularly among elementary school students. This initiative is carried out by students of IAI Pangeran Dharma Kusuma Indramayu through three main programs: flag ceremony training, scouting activities, and school library management. The flag ceremony training aims to foster discipline, responsibility, and respect for national symbols. Scouting activities focus on developing leadership, independence, and teamwork skills rooted in national values. Meanwhile, library management enhances students' access to national literature, strengthening their understanding of the nation's history and struggles. The results of these activities show a significant increase in students' awareness of the importance of nationalism, reflected in their daily behavior at school. Thus, this community service serves as a concrete step in shaping a young generation that is patriotic and nationalistic.